Using materials quality factor BΔΕ∗ for design of thermoelectric materials with multiple bands. (May 2021) - Jia, X.; Li, S.; Zhang, Z.; Deng, Y.; Li, X.; Cao, Y.; Yan, Y.; Mao, J.; Yang, J.; Zhang, Q.; Liu, X.
Abstract: The quality factor B involving carrier mobility, state density effective mass, and lattice thermal conductivity has always been regarded as the guidance for the thermoelectric materials design. However, the traditional quality factor considers a single band and neglects the influence of band gap and the sub-band, whose edge energy is 5 k B T lower than valence band maximum for the p-type or higher than conduction band minimum for n-type semiconductor. In this work, we took into account the band gap and second band based on the three-parabolic-band model and derived an advanced quality factor B Δ E ∗, which is better proportional to the peak ZT values of many compounds with multiple bands. A specific example is also validated based on this quality factor that a highest B Δ E ∗ appears when x = 0.8 for (Yb0.9 Mg0.1 )Mg x Zn2- x Sb2, leading to the highest ZT value at this composition. Graphical abstract: Image 1 Highlights: An advanced thermoelectric quality factor B ΔE ∗ is deviated according to the three-parabolic-band model. ZT has a stronger linear correlation with B ΔE ∗ for the TE materials with multiple bands. B ΔE ∗ is proved robustness in instructing the ZT enhancement in (Yb0.9 Mg0.1 )Mg x Zn2- x Sb2 Zintl compounds.